2014
DOI: 10.1016/j.ijgo.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hyperglycemia and adverse pregnancy outcomes in Dar es Salaam, Tanzania

Abstract: Objective To evaluate maternal glucose levels during pregnancy as a predictor of adverse perinatal outcomes in Dar es Salaam, Tanzania. Methods Random blood glucose measurements were analyzed from 3833 pregnant women enrolled in a randomized trial to assess the impact of multivitamins on pregnancy outcomes in Dar es Salaam between August 2001 and July 2004. Information on maternal and neonatal morbidity was recorded at monthly study visits, delivery, and 6 weeks postpartum. Generalized estimating equations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Hyperglycemia has been suggested to be associated with increased risk of pregnancy complications and adverse prenatal outcomes ( 11 , 26 ). Billionnet et al found that the risk of PTB was 5.8 and 3.1 times higher in type 1 diabetes and type 2 diabetes, separately, than in the no diabetes group ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia has been suggested to be associated with increased risk of pregnancy complications and adverse prenatal outcomes ( 11 , 26 ). Billionnet et al found that the risk of PTB was 5.8 and 3.1 times higher in type 1 diabetes and type 2 diabetes, separately, than in the no diabetes group ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…APO is a complex, multifactorial, physiological outcome in women, and despite decades of research, a clear causal mechanism for APOs has not been established. Studies have reported numerous risk factors for APOs such as malaria [ 6 ], infection [ 7 – 12 ], anaemia [ 13 – 16 ], obesity [ 17 ], hypertension [ 18 ], hyperglycaemia [ 19 ], diabetes [ 20 ], periodontal disease [ 21 ], endometriosis [ 22 ], history of abortion [ 23 ], antenatal complications [ 24 ], antenatal care (ANC) [ 24 ], environmental pollution [ 25 29 ], violence [ 30 ], and other socio-economic disparities [ 31 – 33 ]. In many low- and middle-income countries, access to improved sanitation facilities is limited, but the link between sanitation and APOs has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this low prevalence of poor pregnancy outcomes may be due to the referrals that enabled women to have further checkups and treatments hence, reduced poor pregnancy outcomes. A study done in Dar es Salaam, Tanzania supports these findings that treatment reduces the risk of pregnancy complications hence; hyperglycemic women may have an increased risk of morbidities among women and their newborns (Darling et al, 2014).…”
Section: Discussionmentioning
confidence: 79%